Letter - Schevenels, Walther, b. 1894
032-0103-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe Sch/G. TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter: No. 14th February, 1939. Trades Union Congress, Transport House London S.W.1. Dear Comrades, With reference to your telephone conversation with Comrade Stolz we want to give you the following further information: Our Spanish Committee functioning in Barcelona was composed of the following delegates: Enrique Santiago, Genova, Antonio Perez, Manuel Cordero. This Committee, with the exception of Antonio Perez, who is in Madrid, will continue to function in Limoges. The Committee in the central part of Spain (Valencia, Onteniente, Alicante) is composed of Jose Castro and Amadeo Ribo, and will act on our behalf for the relief in Spain. We are sending you by the same post two photos with the matrices and should be obliged to have the photos back as soon as you have used them, as they are the only copies in our possession. Trusting this information will be useful for you, Fraternally yours, W. Schevenels, General Secretary. PS. I cannot find the photos for the moment, so I am sending only the matrices to-day. 292/946/32/103